FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TEMPE BUNGKUS DAUN DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Nila Kusumawati; Achmad Zaini; Mursidah Mursidah (Jurnal Magrobis, 2019)
The demand for leaf wrapped tempe in Sub District Loa Kulu is influenced by several factors such as income, taste, number family member, expectation future and tempe price. The purposes of this research were to identify and analyze factors influencing the demand of household industry and to know the amount of elasticity of demand of leaf wrapped tempe in Sub District Loa Kulu, District Kutai Kartanegara.This research was conducted from Maret  to April  2017, at Sub District Loa Kulu.The subjects of this research were the exsisting market in Loa Kulu and that sale tempe leaf wrapped.            The data was taken used questionnaires and interviews. Samples taken as many 44 people from 51,453 population.Respondents were taken purposively, who had bought leaf wrapped. Factors demand in the analysis with calculation tool SPSS and the magnitude of elasticity is calculated using manual formula.The result of this showed that income, number family member had significant effect on α = 0.05. While the taste factor, expectation future and price tempe has no significantly effect on α = 0.05. against the demand for leaf wrapped tempe. value of 32.2% means the demand variable tempe leaf wrapped can be explained by income, taste, number family member, expectation future and tempe price, the rest is explained by other factors of 67.8%. And the magnitude of elasticity coefficient on demand of leaf wrapped tempe was 0.08.Demand for leaf wrapped tempe in Sub District Loa Kulu is influenced by several factors such as income, number family member. Magnitude the coefficien of elasticity of demand for leaf wrapped tempe is inelastic category. Keywords: Demand, Leaf Wrapped Tempe, Sub District Loa Kulu